Efektifitas Pembelajaran Daring bagi Siswa dan Orang Tua Siswa di Desa Curug, Kecamatan Bojongsari, Kota Depok - Muhammad Isa Asyrofuddin; Siti Ngainnur Rohmah; Alfi Satria; Syafri Rajabullah; Wildan Taska (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
Since the emergence of the COVID-19 pandemic in Indonesia, the Ministry of Education and Culture has been forced to stop face-to-face learning at schools and on campus. Learning is done online (in the network). Over time, there are many obstacles that are felt by students and parents of students during online learning. This is a strong reason for them to return to face-to-face learning at school. The purpose of this study is to explain the effectiveness of online learning in the Curug Village Community, Bojongsari District, Depok City. The type of research used is qualitative. Data were obtained from observations and surveys of parents of students in Curug Village, Bojongsari District, Depok City. The results of this study indicate that online learning is less effective for students in Curug Village, Bojongsari District, Depok City. This is influenced by the lack of supervision from parents, because not all parents can guide their children (students) during online learning due to other activities at the same time. More attention is needed from the Ministry of Education and Culture to improve the online learning system during this COVID-19 period, if possible, face-to-face learning will be implemented in stages.Keywords: Effectiveness, Online Learning, Parents, Students AbstrakSejak munculnya pandemi COVID-19 di Indonesia, Kemendikbud terpaksa menghentikan pembelajaran tatap muka di sekolah maupun di kampus. Pembelajaran dilakukan secara daring (dalam jaringan). Seiring dengan berjalannya waktu, terdapat banyak kendala yang dirasakan oleh para Siswa dan Orang Tua Siswa selama pembelajaran daring. Hal ini menjadi alasan kuat bagi mereka untuk kembali melakukan pembelajaran tatap muka di sekolah. Tujuan penelitian ini untuk menjelaskan efektifitas pembelajaran daring di lingkungan Masyarakat Desa Curug, Kecamatan Bojongsari, Kota Depok. Jenis penelitian yang digunakan adalah Kualititaf. Data diperoleh dari observasi dan survey kepada Orang Tua Siswa di Desa Curug, Kecamatan Bojongsari, Kota Depok. Hasil penelitian ini menyatakan bahwa pembelajaran daring kurang efektif bagi Siswa di Desa Curug, Kecamatan Bojongsari, Kota Depok. Hal ini dipengaruhi oleh kurangnya pengawasan dari Orangtua Siswa, karena tidak semua orang tua Siswa dapat membimbing Anaknya (Siswa) di saat pembelajaran daring disebabkan kesibukan lainnya dalam satu waktu yang sama. Perlu perhatian lebih dari Kemendikbud untuk meningkatkan sistem pembelajaran daring di masa COVID-19 ini, bila memungkinkan segera kembali diberlakukan pembelajaran tatap muka secara bertahap.Kata Kunci: Efektifitas, Pembelajaran daring, Orang Tua, Siswa